INNOVATIONS AND STANDARD PRACTICES IN DENTAL INSTRUMENTATION: A COMPREHENSIVE REVIEW - Dana Gabriela Budala; Zenovia Surlari; Ionut Luchian; Cosmin Bida; Dragos Fratila; Octavian Tunaru; Monica Mihaela Scutariu; Elena Raluca Baciu; Oana Cristina Cretu; Dragos Ioan Virvescu (Romanian Dental Association for Education, 2024)
This comprehensive review explores the evolution, current state, and future directions of dental instruments, emphasizing innovations, standard practices, and the implications for clinical dentistry. Drawing from an extensive review of literature and patents, this paper categorizes dental instruments into diagnostic, restorative, surgical, endodontic, periodontal, orthodontic, and prosthodontic tools, detailing their specific applications and innovations in design and materials. Special attention is given to technological advancements that enhance functionality, improve durability, and increase patient comfort, including laser technology, CAD/CAM tools, and ergonomic designs aimed at preventing occupational injuries among dental professionals. The paper also addresses the critical importance of sterilization and maintenance protocols for dental instruments to ensure patient safety and prevent cross-contamination. Despite significant progress, challenges such as cost, complexity of maintenance, and adherence to sterilization protocols persist. Looking forward, the paper speculates on the impact of emerging technologies like 3D printing and nanotechnology on the future landscape of dental instrumentation. This review highlights the dynamic nature of dental instrument development and its critical role in advancing dental care, suggesting a need for ongoing research, innovation, and education to fully leverage these tools in clinical practi